Experiential disparities in social VR: uncovering power dynamics and inequality - MacArthur, Cayley; Kukshinov, Eugene; Harley, Daniel; Pawar, Trisha; Modi, Nirali; Nacke, Lennart E. (Frontiers in Virtual Reality, 2024)
Social Virtual Reality (SVR) offers new forms of social interaction, identity expression, and embodied experiences, but it has also revealed significant issues related to social inequalities and unequal power dynamics within virtual worlds. Employing a critical, intersectional approach, we investigate how existing power dynamics and inequalities shape individual experiences and interactions in SVR, shedding light on the differences between the ways that dominant groups and marginalized groups (in relation to race and gender specifically) experience SVR.Analyzing qualitative survey data, we discuss the complex relationship between power dynamics and key SVR affordances, including expectations around perceived anonymity, limited options for avatar customization, practices for self-representation, and actions relating to embodied social interactions. Identifying the specific ways that power and privilege are reenacted in virtual environments, our work calls for deeper engagements with the ways that non-dominant identities and experiences continue to be marginalized in SVR.